SOCIO SCIENTIFIC ISSUE (SSI) BASED LKPD DEVELOPMENT IN LEARNING NATURAL SCIENCE SMP CLASS VII - Astrid Riauda Putriana; Evi Suryawati; Fitra Suzanti; Zulfarina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research aims to produce a valid and practical Socio-Scientific Issue (SSI) based student worksheet (LKPD) on grade VII science learning in junior high school. There are three issues discussed, namely the issue of Unlicensed Gold Mining (PETI) in Kuansing, the issue of waste and the issue of Forest and Land Fires (KARHUTLA). The development research method uses the Plomp model which consists of the preliminary research phase, the prototyping phase and the assessment phase. In the initial investigation phase, a needs analysis is carried out to see the importance of the issues used as the basis for the development of LKPD. The LKPD prototype manufacturing stage was designed based on SSI with validation by experts consisting of lecturers and teachers. Large group test assessment stage on 31 students to see the practicality of the prototype. LKPD validation results are very valid with an average score of 3.4, very practical with a score of 82.9% by the teacher and very practical 81.4% by students. It can be concluded that LKPD based on SSI is valid and practical to be applied in junior high school science learning.